EXPLORING EFL STUDENTS' EXPERIENCES IN USING QUIZIZZ TO ENHANCE WRITING SKILLS AND ITS IMPACT ON WRITING MOTIVATION: A QUALITATIVE STUDY - Septiana; Rahmah Fithriani (International Journal of Cultural and Social Science, 2025)
This study explores the experiences of fifteen tenth-grade students from a secondary school in Medan, Indonesia, using the Quizizz platform to improve their English writing skills and enhance their writing motivation. A phenomenological qualitative approach was employed, with data collected through questionnaires and semi-structured interviews, then analyzed using thematic analysis. The findings indicated that Quizizz had a positive impact on students' motivation, self-confidence, and learning autonomy. The platform’s gamification features and instant feedback encouraged students to write more actively, take risks, and independently correct mistakes. However, the effectiveness of Quizizz was found to depend largely on the teacher-designed tasks and the technical conditions supporting the platform. This study suggests integrating Quizizz into well-designed, sustainable, technology-based writing lessons to foster improved writing skills and sustained motivation among students.